Variants in Mitochondrial ATP Synthase Cause Variable Neurologic Phenotypes. Issue 2 (20th January 2022) - Zech, Michael; Kopajtich, Robert; Steinbrücker, Katja; Bris, Céline; Gueguen, Naig; Feichtinger, René G.; Achleitner, Melanie T.; Duzkale, Neslihan; Périvier, Maximilien; Koch, Johannes; Engelhardt, Harald; Freisinger, Peter; et al.
Abstract : Objective: ATP synthase (ATPase) is responsible for the majority of ATP production. Nevertheless, disease phenotypes associated with mutations in ATPase subunits are extremely rare. We aimed at expanding the spectrum of ATPase‐related diseases. Methods: Whole‐exome sequencing in cohorts with 2, 962 patients diagnosed with mitochondrial disease and/or dystonia and international collaboration were used to identify deleterious variants in ATPase‐encoding genes. Findings were complemented by transcriptional and proteomic profiling of patient fibroblasts. ATPase integrity and activity were assayed using cells and tissues from 5 patients. Results: We present 10 total individuals with biallelic or de novo monoallelic variants in nuclear ATPase subunit genes. Three unrelated patients showed the same homozygous missense ATP5F1E mutation (including one published case). An intronic splice‐disrupting alteration in compound heterozygosity with a nonsense variant in ATP5PO was found in one patient. Three patients had de novo heterozygous missense variants in ATP5F1A, whereas another 3 were heterozygous for ATP5MC3 de novo missense changes. Bioinformatics methods and populational data supported the variants' pathogenicity. Immunohistochemistry, proteomics, and/or immunoblotting revealed significantly reduced ATPase amounts in association to ATP5F1E and ATP5PO mutations. Diminished activity and/or defective assembly of ATPase was demonstrated by enzymatic assays and/or immunoblotting in patient samples bearing ATP5F1A ‐p.Arg207His, ATP5MC3 ‐p.Gly79Val, and ATP5MC3 ‐p.Asn106Lys. The associated clinical profiles were heterogeneous, ranging from hypotonia with spontaneous resolution (1/10) to epilepsy with early death (1/10) or variable persistent abnormalities, including movement disorders, developmental delay, intellectual disability, hyperlactatemia, and other neurologic and systemic features. Although potentially reflecting an ascertainment bias, dystonia was common (7/10). Interpretation: Our results establish evidence for a previously unrecognized role of ATPase nuclear‐gene defects in phenotypes characterized by neurodevelopmental and neurodegenerative features. ANN NEUROL 2022;91:225–237